EMOTIONAL SELF-PRESENTATION ON WHATSAPP: ANALYSIS OF THE PROFILE STATUS - Maíz-Arévalo, C. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2018)
Self-presentation can be defined as “the process through which individuals communicate an image of themselves to others” (Yang and Brown, 2015: 404) and it is an essential part of human communication. Self-presentation has been widely studied both in face-to-face communication and online. Most online research, however, has focused on social networking sites, blogs, chatrooms, etc. while less attention has been paid to other online means of communication such as WhatsApp despite the growing im-portance of WhatsApp as a means of communication. The present paper aims to redress this imbalance by analysing self-presentation on WhatsApp; more specifically, by paying attention to emotional self-pre-sentation in profile status. To that purpose, a corpus of 206 WhatsApp statuses was gathered in Spanish. Results show the existence of recurrent patterns connected to variables such as sex1 or age, which play a crucial role in determining the emotions users choose to display in their profile status.